Young male mating success is associated with sperm number but not with male sex pheromone titres. Issue 1 (December 2015) - Kehl, Tobias; Dublon, Ian; Fischer, Klaus
Abstract Background Intraspecific communication is of crucial importance throughout the animal kingdom and may involve a combination of visual, gustatory, olfactory and acoustic cues. Variation in male sex pheromone amount and composition may convey important information to female conspecifics, for instance on species identity or age. However, whether increased male pheromone titres are associated with fitness benefits for the female, thus indicating a role as an honest signal, is under debate. Results Against this background, we tested in the butterflyBicyclus anynana (1) whether young males being successful or unsuccessful in gaining a mating differed in sex pheromone titres and (2) for associations between male pheromone titres and spermatophore mass, eupyrene sperm number, and a variety of female and offspring life-history traits. Successful and unsuccessful males did not differ in pheromone titres, however eupyrene sperm number was much higher in successful males. Pheromone titres were not associated with any fitness-related female or offspring trait measured in our study, though correlation analyses yielded evidence for trade-offs among specific traits. Patterns did not differ among control and olfaction-blocked females. Conclusion Therefore, we suggest that in youngB. anynana pheromone titres do not indicate male quality.